Are large-scale hydroelectric dams inherently undemocratic?. (November 2021) - García, María Alejandra; Castro-Díaz, Laura; Villamayor-Tomas, Sergio; Lopez, Maria Claudia
Highlights: Resettlement policies of hydroelectric dams have low citizen participation. We find pathways explaining deficits in citizen participation in dam projects. Dams built under autocracies before 2000 have deficits in participation. Large dams with high economic interests built in democracies also have deficits in participation. Abstract: Construction of large-scale hydroelectric dams has increased in recent decades in the Global South and emerging economies. Population resettlement is one of the most severe socioeconomic impacts caused by dam construction. Processes aiming to mitigate its impacts and restore livelihoods are often described as inadequate. The resettlement process' ineffectiveness could be explained by persistent deficiency in citizen participation, which is also a sign of the impacted population not being able to participate in the process affecting their lives. Our research presents a medium-N comparative study showing the pathways explaining deficiency of participation across 23 large-scale hydroelectric dams in Asia, Africa, and Latin America. We conducted a fuzzy-set Qualitative Comparative Analysis based on information from a qualitative meta -analysis and secondary sources. Our results suggest that there are at least two scenarios to explain deficiency in participation. The first scenario includes dams constructed during autocracies, mostly before the release of the World Commission on Dams guidelines. The second scenario involves the largest dams in our analysis, with high economic and political interests at stake built under both autocratic and democratic regimes, despite the presence of what we categorized as effective forms of public opposition to the project and resettlement process. We discuss features that make large hydroelectric dams less participatory or inherently undemocratic in the Global South.